Besedni red v slovenskih kemijskih terminoloških besednih zvezah - Štumberger, Saška (Jezik in slovstvo, 2025)
The article examines chemical terminology in Slovenian and compares word order in Slovenian, German, and English. It focuses on chemical terms that are multi-word expressions in at least one of the languages. In the 19th century, chemical terms in the works of Matija Vertovec were listed alongside their German equivalents. The influence of German is reflected in the structure of the terms, with acid names being single-word expressions, such as vogelnokislina (carbonic acid) and žeplokislina (sulfuric acid). After World War I, the establishment of the Kingdom of Serbs, Croats, and Slovenes led to efforts for a unified Yugoslav chemical terminology. The German influence is evident in the attempt to preserve single-word terms modelled after German compounds, such as jodkislina (iodic acid). Such terminology was intended for scientific discourse and higher education, while multi-word expressions like jodova kislina were planned for secondary school teaching. The material in the Chemical Dictionary demonstrates the linguistic independence of Slovenian. German compounds in Slovenian are expressed as multi-word phrases, which, for clarity, often include a nominal post-modifier, as in anomalija vode (water anomaly). Terminological structures with both pre- and postmodifiers, such as začasna trdota vode (temporary water hardness), can also be explained by the need for clarity. The influence of English is evident in multi-word terms with a nominal premodifier, such as alfa železo (alpha iron), which also has variant forms like železo alfa and alfa-železo. The placement of the nominal postmodifier reflects Slovenian syntax, while the hyphenated form follows the German model (Alpha-Eisen).
Keywords: angleščina; besedni red; besedotvorje; Chemical Dictionary; chemical terminology; chemistry; desni prilastek; English; German; German compounds; kemija; kemijska terminologija; Kemijski slovar; multi-word term; nemščina; nemške zloženke; postmodifier; Slovenian; slovenščina; terminologija; terminology; večbesedni termin; word formation; word order